Human thermal adaptation based on university students in China's severe cold area. (3rd April 2017) - Wang, Zhaojun; Ning, Haoran; Zhang, Xuexiang; Ji, Yuchen
Abstract : A field investigation was carried out in a university campus in Harbin winter to study students' thermal comfort and adaptation. Thirty students were selected as the participants. They were tracked and surveyed and their environmental parameters were monitored in dormitories and classrooms. The results show that the indoor air temperatures were close to the upper limit 24°C in ASHRAE 55 Standard (ASHRAE2013 ) when the relative humidity and air speed met the standard in both environments. The 90% acceptable temperature range was 19.7°C–23.2°C in dormitories and 16°C–22.4°C in classrooms. Meanwhile, it is found that the participants' thermal responses were evidently discrepant in different built environments. The thermal neutral temperatures were always lower than the indoor temperatures in any heating phase, and they were much lower in classrooms than in dormitories. The mean thermal sensation was basically higher than predicted mean vote (PMV) during the whole space heating period. A thermal adaptation to the cold climate was presented on participants in this field study. However, their acclimatization had been gradually undermined with a long-term thermal exposure to the artificial heating environment. Human thermal adaptability to coldness should be well considered in winter and a high thermal comfort zone should be avoided. If the thermal neutral temperature could be used instead of the current indoor air temperature for space heating, 3.4% and 12% heating energy would be saved, respectively, in dormitories and classrooms.